A porohyperviscoelastic model for the shear wave elastography of the liver. (May 2021) - Zheng, Yang; Jiang, Yuxuan; Cao, Yanping
Highlights: A porohyperviscoelastic model is presented to address the shear wave elastography of soft tissues with emphasis on the liver; An analytical solution has been derived to reveal the dependence of the wave velocity on the constitutive parameters and deformation of the solid matrix generated by the internal pressure; The model and solution help understand the dispersion of the shear waves in porohyperviscoelastic soft tissues; The analysis reveals that both the hyperelastic and viscoelastic deformation behaviors of the solid matrix are responsible for the pronounced effect of the internal pressure on the shear wave velocity. Abstract: Shear wave elastography (SWE) enables the probing of the mechanical properties of soft tissues in vivo and has been demonstrated to be a promising technique for the diagnosis of diseases such as staging liver fibrosis, evaluating artery stiffening, and detecting cancers. In this study, a porohyperviscoelastic model is presented to address the shear wave elastography of soft tissues with emphasis on the liver. Based on this constitutive model, an analytical solution has been derived to reveal the dependence of the wave velocity on the constitutive parameters and deformation of the solid matrix generated by the internal pressure. The model and solution not only help understand the dispersion of the shear waves in porohyperviscoelastic soft tissues such as the liver, but also reveal that both the hyperelastic and viscoelastic deformation behaviors of the solid matrix may play an important role in the pronounced effect of the internal pressure on the shear wave velocity, as observed in experiments. The analysis results are expected to advance our understanding of SWE and facilitate its use in clinics.